Influence of EM4 Probiotic In Artificial Feed With Different Doses To Growth and Life of Red Tilapia (Oreochromis niloticus) In Brackish Water By - Lumbanbatu, Pretty A; Mulyadi, Mulyadi; Pamukas, Niken Ayu (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This research was conducted from April 5th, 2018 – May 10th, 2018 in Unit Implementer of Technical Territory, Teluk Papal village, Bengkalis-Riau. The purpose of this research was to knew the best dose of probiotic EM4 and influence in artificial feed to increase the growth of red tilapia fish (Oreochromis niloticus)and to determine the effect of giving probiotics in brackish water. The method of this research was used a Completely Randomized Design (CRD) with one factor,fivelevel treatments and three replications. Each treatments was given a probiotic addition of feedapplied P1(0 ml/kg), P2(5 ml/kg), P3 (10 ml/kg), P4(15 ml/kg) and P5(20 ml/kg). The results showed that the best treatment contained in P4 (15 ml/kg)with weight growth of 8,542g, absolute growth of 3,63 cm, specific growth rate of 4,501%, feed efficiency of 74,293%, feed conversion of 1,346 and survival rate of 100%. Keywords :Brackish water, EM Growth, Probiotics,Red tilapia fish(Oreochromis niloticus)